Análise de medidas lineares e volumétricas de seios paranasais de indivíduos brasileiros com vistas à identificação humana - Barros, Franciéllen De [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Foram avaliadas as possibilidades de identificação humana por meio da análise dos seios paranasais, e na estimativa do sexo, idade e ancestralidade (Publicação 1), de imagens 2D e 3D dos seios frontais e o papel do ortodontista nesse contexto (Publicação 2). Através do software DDS-Pro®, foram realizadas mensurações volumétricas dos seios maxilar (Publicação 3) e esfenoidal (Publicação 5), e mensurações lineares dos seios maxilar (Publicação 4), esfenoidal (Publicação 6) e frontal (Publicação 7), utilizando imagens de tomografia computadorizada de feixe cônico de indivíduos brasileiros, verificando a existência de diferenças entre os lados, e a correlação das medidas com sexo, idade, cor da pele e estado nutricional. A análise dos seios é uma ferramenta útil para a identificação e estimativa de sexo, idade e ancestralidade (1). A análise 2D e 3D dos seios frontais são de grande valia para a identificação (2). Não houve diferenças entre os lados, os sexos e o IMC, mas houve diferenças entre as idades e na cor de pele (3). Houve diferenças entre os lados, os sexos, as idades, todavia não houve diferenças entre a cor de pele e o IMC (4). Não houve diferenças entre os lados, os sexos e a cor de pele, mas houve diferenças entre as idades e IMC (5). Não houve diferença entre os lados, a cor de pele e o IMC, entretanto houve diferenças entre os sexos, as idades (6). Houve diferenças entre os lados, os sexos, as idades, contudo não houve diferenças entre cor de pele e IMC (7).

The possibilities of human identification were evaluated by analyzing paranasal sinuses and estimating sex, age, and ancestry (Publication 1-P1) of 2D and 3D images of frontal sinuses. It also investigated the role of orthodontists in this context (Publication 2-P2). Volumetric measurements of maxillary (Publication 3-P3) and sphenoid (Publication 5-P5) sinuses and linear measurements of maxillary (Publication 4-P4), sphenoid (Publication 6-P6), and frontal (Publication 7-P7) sinuses were performed with the DDS-Pro™ software, using CBCT images of Brazilian individuals. The study verified potential differences between the sides and a correlation of measurements to sex, age, skin color, and nutritional status. It was found that: P1- Sinus analyses can be used for identification and sex, age, and ancestry estimations. P2- The 2D and 3D analyses of frontal sinuses are valuable for identification, and orthodontists must be aware of this possibility. P3- There were no differences for the sides, sexes, and BMI, but there were differences for ages and skin color. P4- There were differences for the sides, sexes, and ages, but there were no differences between skin color and BMI. P5- There were no differences for the sides, sexes, and skin color, but there were differences between age and BMI. P6- There were no differences for the sides, skin color, and BMI, but there were differences between the sexes and ages. P7- There were differences for the sides, sexes, and ages, but there were no differences between skin color and BMI.
Analysis of linear and volumetric measurements of paranasal sinuses of Brazilian individuals with a view to human identification
Keywords: Ciências Forenses; Odontologia Legal; Seios paranasais; Tomografia Computadorizada de Feixe Cônico; Radiologia; Forensic Sciences; Forensic Dentistry; Paranasal Sinuses; Cone-Beam Computed Tomography; Radiology